Kekuatan Keterangan Saksi Verba Lisan (Saksi Penyidik) Dalam Kitab Undang-Undang Hukum Acara Pidana - Mayang Sekar Ningrum Nasution; Siti Hairani Siregar; Fatimah Zahara (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Verbal witnesses are investigators whose participation in court is not mandated by the Criminal Procedure Code, but who are frequently presented in court when the defendant withdraws all or part of the minutes of examination (BAP) filed before investigators at trial. “The goals of this study are to determine the legitimacy of verbal witness statements and their link to” Article 184 of the Criminal Procedure Code concerning legal evidence, as well as to determine how verbal witness statements influence judge choices in Indonesian cases today. This is normative legal research, also known as research on legal systematics. Research on legal systematics is a study of legislation or written law. The goal is to identify the fundamental conditions of rights and responsibilities, legal events, legal connections, and legal objects. The study and discussion results indicate that: first, the statement of an oral verbal witness is valid if given under oath, and the judge's statement from the verbal witness can be used as evidence in court; second, the testimony of verbal verb witnesses is limited to what is recorded by the investigative witnesses during the investigation process, so it becomes the full responsibility of the judge to conclude that the revocation of the warrant is justified. Keywords: statement, verbal witnesses, KUHAP